Perbandingan Kinerja Campuran Aspal Porus Menggunakan Spesifikasi Australia (AAPA) dan California (CalTrans) dengan Serbuk Parutan Limbah Ban Karet - Julang Angkoso; Miftahul Fauziah (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Porous asphalt is an open graded hot mix asphalt with a small percentage of fine aggregate and a large percentage of coarse aggregate. Porous asphalt is an asphalt mixture that is being developed for wearing course construction. The aim of this research is to analyze the effect of adding rubber tire powder on the performance of the Asphalt Porous-Wearing Course. In this research two standard gradations for porous asphalt were used, namely Australian gradation (AAPA) and California gradation (CalTrans) with the addition 0%, 2%, 4%, and 6% of rubber tire powder. Based on the research carried out, it can be seen that the addition of rubber tire powder to a mixture with AAPA gradation is better in terms of its ability to accept loads without experiencing deformation (stability) and the possibility of the mixture being able to withstand maximum loads to prevent traction failure (ITS). Meanwhile, mixtures with Caltrans gradations are better in terms of resistance to wear (CL), homogeneous mixing of asphalt and aggregate (AFD), and ability to resist cracking (TSR). The addition of rubber tire powder was not able to improve the strength due to immersion at extreme temperatures (IRS) in a mixture of both gradation specifications.